The moral dilemmas of fighting terrorism and guerrilla groups - Caron, Jean-François (Facing contemporary terrorism, 2023)
The Moral Dilemmas of Fighting Terrorism and Guerrilla Groups discusses the most important ethical dilemmas associated with the fight against terrorist organizations and guerilla groups by providing readers with a rigorous, yet accessible analysis of how these forms of violence can be justified and how they ought to be fought by entities targeted by groups resorting to these strategies. It will be valuable to anyone interested in understanding the main ethical questions associated with these forms of political violence and the way they can be addressed. After providing conceptual clarifications that will allow the reader to distinguish between terrorism and guerrilla warfare, it explains and discusses what the criteria are that can justify resorting to lethal violence on the part of the latter group as well as the criteria that can determine the identity of those who can legitimately be targeted by these groups. The book analyzes when terrorists ought to be targeted and how this can be done, focusing on the inherent problems associated with the solutions that are normally used against state actors in order to prevent attacks on their part, namely what can be coined as "non-violent alternatives to war", such as economic or diplomatic sanctions, arm embargoes and non-violent resistance and, on the other hand, preemptive attacks.